A high molecular weight hyaluronic acid biphasic dispersion as potential therapeutics for interstitial cystitis. Issue 6 (26th October 2020) - Rooney, Peadar R.; Kannala, Vijaya Krishna; Kotla, Niranjan G.; Benito, Ana; Dupin, Damien; Loinaz, Iraida; Quinlan, Leo R.; Rochev, Yury; Pandit, Abhay
Abstract: Interstitial cystitis (IC) is a progressive bladder disease characterized by increased urothelial permeability, inflammation of the bladder with abdominal pain. While there is no consensus on the etiology of the disease, it was believed that restoring the barrier between urinary solutes and (GAG) urothelium would interrupt the progression of this disease. Currently, several treatment options include intravesical delivery of hyaluronic acid (HA) and/or chondroitin sulfate solutions, through a catheter to restore the urothelial barrier, but have shown limited success in preclinical, clinical trials. Herein we report for the first time successful engineering and characterization of biphasic system developed by combining cross‐linked hyaluronic acid and naïve HA solution to decrease inflammation and permeability in an in vitro model of interstitial cystitis. The cross‐linking of HA was performed by 4‐arm‐polyethyeleneamine chemistry. The HA formulations were tested for their viscoelastic properties and the effects on cell metabolism, inflammatory markers, and permeability. Our study demonstrates the therapeutic effects of different ratios of the biphasic system and reports their ability to increase the barrier effect by decreasing the permeability and alteration of cell metabolism with respect to relative controls. Restoring the barrier by using biphasic system of HA therapy may be a promising approach to IC.